Embryo rescue from non-viable seeds for preservation of wheat (Triticum aestivum) germplasm - Ganguli, Smritimala; Sen-Mandi, Swati (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during the winter season of 1992-93 to adopt a very simple method of replenishing germplasm ofwheat at (Triticum aestivum L. emend. Fiori & Paol.), which is under threat of extinction due to post-harvest deterioration.A high number of embryos from naturally aged stock of 50% viability could be made to germinate with root and shoot whenincubated aseptically on agar + sucrose for prolonged periods (40 days). The seedlings with plumule sheath without leaf didnot develop root (at least up to 40 days). Those developing root even 35 days after incubation when transferred to fielddeveloped into normal plantlets and produced viable seeds.